A School for thinking - Furth, Hans G (Journal of All India Institute of Speech and Hearing)
It is hard to know where to start when one has a lot to say, so I’ll start without beating around the bush. Would you like to see the condition of learning disorder eliminated? I will suggest to you a plan about this. There is one sure thing we know about learning disorders: it is a maladaptive response to the school system. Now it is my thesis that this maladaptive response could be changed if we changed the educational environment of the early school years. I say this without any critical spirit on my part, fully knowing that change is of course a very difficult process. But it seems that we as scientists have to be honest and straightforward and put the finger on the principal cause rather than on secondary and tertiary causes. We should state a desirable goal, even if its implementation requires all kinds of political, social, and academic changes, which are not easy to come by. I am not suggesting then that an educational change like the one I am proposing can take place overnight; but I would like to talk to you as a develop- mental psychologist who knows something about what intellectual development means